The importance of public investments and institutions for the functioning of food markets in developing countries - Hazell, Peter B. R.; Fan, Shenggen (University Library Groningen, 2002)
The papers presented in this CDS Research Report centre around three PhD studies in the CDS research theme groups on Food Security and Food Markets in West Africa. They discuss problems of food security and food markets in Burkina Faso. The studies were the subject of two international workshops at the University of Groningen, one on October 25, 2000 and one on January 30, 2002. This Research Report publishes the key papers of these two workshops... This book gives a nice overview of the present research activities of the CDS research theme group on Food Security and Food Markets. The authors apply advanced quantitative techniques, while showing at the same time the relevance of the research results for development policies in Burkina Faso as well as elsewhere.